Teacher education and its relation to inclusive education: challenges to theoretical experience in pedagogical praxis - Valdelúcia Alves da Costa (Universidade Federal de Santa Maria (UFSM), 2015)
Considering research results, this paper aims to problematize teachers formation and their relationship with inclusive education, while analyzing challenges to theoretical experience in inclusive pedagogical praxis. Both problematic regarding analysis, turn to a central question: even considering recent advances in processes of teacher formation towards inclusive education, it is still necessary to develop teacher formation in its theoretical dimension, in overcoming pseudo idea that teaching praxis and canonical methods of teaching, to be thought of as an end in themselves, but also sufficient in confronting and overcoming social limits, imposed historically to teachers as human limits. This pedagogical praxis trivializes and / or denies human demand for theoretical formation, which enables both thinking about political investigative role opposed to segregation of students with disabilities in public school and in other social instances. Admitting this formative perspective, by theoretical experience will help in the humanization of teachers and students with and without disabilities, to counter domination and social unconsciousness, marks of class society, attending the public school.